2005
DOI: 10.1097/01.prs.0000169717.84221.d7
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Vascular Architecture of the Free TRAM Flap Using Intraoperative Ex Vivo Angiography

Abstract: Because the cephalic half of zone 2 and all of zone 4 remain unstained, these areas are prone to skin or fat necrosis, especially in high-risk patients. Ex vivo angiography, by providing specific information about the individual flap and by reflecting its flow physiology, enables one to observe and to chart the vascular architecture of free TRAM flaps nourished by the deep inferior epigastric artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…The BF PET was lower in zone I than in zones II and III, which somewhat contrasts with previous results. 13,37,38 The explanation for this controversy could be different monitoring methods used in these previous publications measuring cutaneous perfusion and not BF PET . 13,33 Furthermore, the greater heterogeneity in zones I and II in comparison to zone III supports the assumption that monitoring blood flow from the more superficial parts of the flap might not present the perfusion of the whole flap.…”
Section: Discussionmentioning
confidence: 86%
“…The BF PET was lower in zone I than in zones II and III, which somewhat contrasts with previous results. 13,37,38 The explanation for this controversy could be different monitoring methods used in these previous publications measuring cutaneous perfusion and not BF PET . 13,33 Furthermore, the greater heterogeneity in zones I and II in comparison to zone III supports the assumption that monitoring blood flow from the more superficial parts of the flap might not present the perfusion of the whole flap.…”
Section: Discussionmentioning
confidence: 86%
“…Although few in number, subsequent studies have varied in their accounts of this branching pattern. Three separate studies, with two of these from the same research group, describe a uniformly bifurcating pattern of the DIEA (Ohjimi et al, 2002(Ohjimi et al, , 2005Tansatit et al, 2006). Of these, two studies used intraoperative ex-vivo angiography for analysis and the other was a dissection study in embalmed cadavers.…”
Section: Named Source Vesselsmentioning
confidence: 94%
“…Moreover, they found that all periumbilical and infraumbilical perforators are derived solely from the DIEA. Further anatomical studies have added to the literature, utilizing a combination of dissection, radiography, and angiography to describe the location of these perforators (Itoh and Arai, 1993;Konerding et al, 1997;Stokes et al, 1998;Heitmann et al, 2000;El-Mrakby and Milner, 2002;Ohjimi et al, 2002Ohjimi et al, , 2005Tansatit et al, 2006).…”
Section: The Musculocutaneous Perforators Of the Dieamentioning
confidence: 96%
See 1 more Smart Citation
“…In highly obese subjects, fat necrosis extended even to the craniad side of zone II. Ohjimi et al 11,12 reported that blood circulation is poorer in the craniad than in the caudal side of zone II, suggesting that this region has a higher risk of fat necrosis in obese patients. In our series of MS-2 free TRAM flaps, 7 of 8 patients (87.5%) who had partial fat necrosis were obese with BMI of 25 or above.…”
Section: Discussionmentioning
confidence: 97%